Delignification Pretreatment of Palm-Press Fibres by Chemical Method - Tong, Chow Chin; Hamzah , N. M. (1989)
The chemical composition of the untreated palm-press fibres was estimated to be 39.9% cellulose, 28.9% hemicellulose, 20.3% lignin and 3.6% ash content. The concentrations of the chemicals used in the treatment of the fibres were 1.5% each of NaOH, Ca(OH)2' KOH, Na2COy 5.0% CO(NH)2 and aqueous ammonia solution. Of the chemicals tested. NaOH was the most efficient, having removed 60% of the lignin from the fibres after treatment for 24 hours using the spraying method. Comparative percentages for other chemicals tested were Na2CO/49%), NHpH (40%), Ca(OH)2 (38%), KOH (27%) and CO(NH)2 (21 %). The cellulose and hemicellulose content remained almost unchanged even after a prolonged period of treatment lJy these chemicals. The ash content was higher in fibres treated with NaOH and urea. The soaking method dissolved higher lignin content compared to the spraying method.